Patrimonial violence: A study of women’s property rights in Ecuador - Deere, Carmen Diana; Contreras, Jacqueline; Twyman, Jennifer (SAGE Publications, 2014)
Patrimonial violence, defined minimally as the violation of women’s property rights, is increasingly recognized as a form of gender violence, along with physical, psychological, and sexual violence. Research in Ecuador on the extent to which women are aware of their property rights and the situations in which patrimonial violence is most likely to occur shows that, while most women seem to be aware of certain fundamentals, there are many misconceptions, particularly regarding the status of individual property. Women’s lack of legal knowledge often undermines their ability to obtain their rightful share of the division of property upon separation, divorce, or widowhood. Moreover, patrimonial violence is often aggravated by the presence of other forms of violence against women.La violencia patrimonial, definida mínimamente como la violación de los derechos de propiedad de las mujeres, se reconoce cada vez más como una forma de violencia de género, a la par que la violencia física, psicológica y sexual. Investigaciones sobre el grado en que las mujeres son conscientes de sus derechos de propiedad y las situaciones en las que es más probable que se produzca violencia patrimonial en Ecuador muestran que, mientras que la mayoría de las mujeres parece estar conscientes de ciertos fundamentos, manejan muchas ideas equivocadas, particularmente con respecto al estado de la propiedad individual. Su falta de conocimiento legal a menudo socava su capacidad de obtener una parte justa de la división de bienes ocurrida a raíz de una separación, divorcio o viudez. Lo que es más, la violencia patrimonial a menudo se ve agravada por la presencia de otras formas de violencia contra la mujer.